Thermally stimulated luminescence studies of undoped and doped CaB₄O₇ compounds - Manam, J.; Sharma, S.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Thermoluminescence of undoped and doped CaB₄O₇ with activators such as Cu and Mn has been investigated. The polycrystalline samples of undoped and doped CaB₄O₇ are prepared by melting method. The formation of CaB₄O₇ compound is checked by X-ray diffraction study and the compound is found to have orthorhombic structure at room temperature. The TSL studies of undoped CaB₄O₇ sample shows two glow peaks at 150°C and 265°C and one shoulder at around 190°C. The TSL studies of Cu doped CaB₄O₇ sample also shows two glow peaks at 160°C and 270°C and a shoulder at around 230°C whereas the TSL glow curves of Mn doped CaB₄O₇ has only one single strong glow peak at 135°C. A comparative TSL studies of these compounds shows that CaB₄O₇ compound doped with Mn is the most sensitive and the TSL intensity is enhanced by about 40 times when compared with the TSL intensity of undoped CaB₄O₇ compound. The trap parameters namely order of kinetics (b), activation energy (E) and frequency factor (s) associated with the 135°C glow peak of CaB₄O₇: Mn phosphor are determined using isothermal decay and glow curve shape (Chen's) methods.